2010
DOI: 10.1084/jem.20091962
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate suppression of B cell lymphoma by PTEN and SHIP phosphatases

Abstract: Mice lacking both PTEN and SHIP phosphatases develop spontaneous B cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…These results are consistent with data, suggesting that signaling through the PI3K pathway, in particular downstream of the pre-BCR, is important for early B cell development especially for the survival and differentiation of pre-B cells (Werner et al, 2010). Furthermore, increased PTEN expression in the absence of miRNAs may also contribute to the elevated level of the pro-apoptotic protein Bim (Miletic et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with data, suggesting that signaling through the PI3K pathway, in particular downstream of the pre-BCR, is important for early B cell development especially for the survival and differentiation of pre-B cells (Werner et al, 2010). Furthermore, increased PTEN expression in the absence of miRNAs may also contribute to the elevated level of the pro-apoptotic protein Bim (Miletic et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…B cell purification and in vitro stimulation were performed as described (Miletic et al, 2010). For survival assays, purified splenic or lymph node B cells were plated at a concentration of 1×10 6 cells/mL in 10% media.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies of the impact of BAFF depletion on lymphoma progression are limited. However, we found that primary B cells tumors arising from the co-inactivation of Pten and Ship can progress in the absence of BAFF (138). Thus, based on murine models, one may predict that malignant B cells displaying constitutive activation of canonical or non-canonical NF-κB or PI3K may not be responsive to anti-BAFF treatment.…”
Section: Baff-r Signaling and Diseasementioning
confidence: 97%